Clinical pathways in patients with ischaemic stroke: Estimating mean length of stay and hospital costs - Yuwono, Reinaldo Bobby; Zulfikar, Taufik; Malik, Rahadian (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Effective and efficient healthcare services have become one of the priorities in the global health system, including in Indonesia. In an effort to improve quality and efficiency of care, various initiatives have been implemented by hospitals, one of which is the application of Clinical Pathways (CP). A Clinical Pathway is a systematic approach designed to provide evidence-based guidelines in managing patients with specific conditions, with the goal of improving quality, efficiency, and patient safety. Purpose: To analyze the effectiveness of clinical pathways on length of stay (LOS) and its implications for hospital costs in ischemic stroke patients. Method: This quantitative, analytical, observational study used a cross-sectional approach. Data collection was conducted retrospectively using secondary data from patient medical records, Clinical Pathway documents, and the Hospital Information System (SIMRS). This included all inpatients with ischemic stroke treated by the Social Security Administration at Hermina Hospital Solo during 2024. The sample size was determined using the Slovin formula with a 5% margin of error, resulting in a sample of 170 respondents. Results: Regression analysis showed that CP significantly affects LOS, with a regression coefficient indicating that increased adherence to CP can reduce LOS. LOS also has a significant effect on hospital costs, with a positive regression coefficient, meaning the longer the LOS, the higher the hospital cost. However, CP does not have a direct effect on hospital costs. Path analysis revealed an indirect effect of CP on hospital costs through LOS, indicating that improved CP adherence can reduce hospital costs by shortening LOS. Conclusion: That higher adherence to CP can shorten LOS and indirectly lower hospital costs. Hospital management is expected to conduct regular socialization, evaluation, and monitoring of CP implementation to achieve optimal service efficiency and cost control.